AQIDAH AKHLAK TEACHER STRATEGIES FOR CULTIVATING NOBLE CHARACTER IN GRADE IX STUDENTS AT MTS AR RAHMANIYAH - Yusup Al Jailani; Reffy Ananda Rizki; Nadra Ulfah; Rudini; Anna Navita Syairoh (JF Publisher, 2025)
In the era of globalization, adolescents face significant moral challenges, including behavioral issues that persist despite ongoing character education efforts in Islamic schools. This qualitative study explores the strategies employed by the Aqidah Akhlak teacher to cultivate noble character among Grade IX students at MTs Ar Rahmaniyah, South Tangerang City. Data were collected through semi-structured interviews with teachers, students, and school administrators, alongside direct classroom observations. The findings reveal that character cultivation involves a comprehensive approach integrating theoretical instruction with practical application, teacher exemplification of virtuous behavior, and collaborative efforts among school leadership, homeroom teachers, parents, and the foundation. Key strategies include strategically timed character-building programs, regular guidance sessions, and extracurricular religious activities such as murrotal. While observable improvements in students' moral awareness occurred, persistent negative behaviors influenced by socioeconomic marginalization and limited institutional resources remained challenging. The study demonstrates that effective character formation requires teachers to function as moral exemplars, mentors, and motivators beyond mere knowledge transmission. The teacher's role proves critical yet dependent on adequate institutional support and sustained family collaboration. Recommendations include enhanced professional development for teachers, strengthened school-family partnerships, and systematic resource allocation to bridge the gap between theoretical moral education and behavioral transformation in urban Islamic educational settings.